Evaluation of different probiotic strains for growth performance and immunomodulation in Pacific white shrimp Penaeus vannamei Boone, 1931 - Sundaram, M.; Panigrahi, A.; Ganesh, J.; Nila Rekha, P.; Sivagnanam, S.; Rajamanickam, S.; Gopal, C. (Indian Journal of Fisheries, 2018)
The use of antibiotics in aquaculture can prevent certain diseases, however, its use is highly restricted due to several environmental and human health problems like development of antibacterial resistance. Probiotics are widely used for improving production of aquatic animals by means of improving water quality as well as by nutritional and immune modulation in animals thus, helping in preventing diseases. The present study was aimed to evaluate different strains of probiotics viz., a commercial probiotic, Bacillus subtilis, Enterococcus sp., Lactobacillus casei, Lactobacillus rhamnosus, Saccharomyces cerevisiae and Saccharomyces boulardii on the growth, microbial load and immunomodulatory performance of the Pacific white shrimp, Penaeus vannamei. Seven probiotic feeds each containing 5 x 109 CFU ml-1 of respective probiotics kg-1 of feed were prepared by top coating on a pellet feed containing 35% protein and duration of the experiment was 75 days. All of the 6 selected strains of probiotics except the commercial one influenced the growth significantly when fed to the shrimp, compared to control group. Specific growth rate (SGR), average daily growth (ADG) and survival rate were observed to be higher in probiotic fed groups. Maximum growth was recorded in S. cerevisiae fed groups (8.05±0.21 g), followed by B. subtilis (7.65±0.21 g), while the control animals showed an average growth of 4.85±0.49 g with percentage improvement in the range of 50-95% when compared to all other treatments. Total heterotrophic count significantly (p<0.05) increased in the rearing water of B. subtilis treated group (8.995± 0.021 x 103 cfu ml-1) when compared to that of control (5.475± 0.003 X 103 cfu ml-1) and total vibrio load was greatly reduced in B. subtilis (1.42 ± 0.04 x 103 cfu ml-1) and S. cerevisiae (1.47 ± 0.01 x 103 cfu ml-1) treated water compared to control (4.265 ± 0.06 x 103 cfu ml-1). Nonspecific immunity in terms of total haemocyte count (THC) was found to be significantly (p<0.05) higher in B. subtilis (12.4±0.8 106 cells ml-1) treated group while higher (p<0.05) prophenoloxidase (pro PO) activity was recorded in S. erevisiae (0.132±0.001 units min-1 mg protein-1) and B. subtilis (0.130±0.002 units min-1 mg protein-1) treated groups. The probiotic effect was found to be beneficial for better growth and immunomodulation, which was however found to be strain-specific.